Up-to-date comorbid anxiety and depressive syndromes among servicemen participating in combat operations - О. М. Tkalenko; I. M. Tkachuk; M. V. Oliinyk; A. K. Sokolyuk; S. V. Latishenko (Український журнал військової медицини)
Purpose: to study the prevalence of comorbid anxiety and depressive syndromes among the military personnel participating in combat operations who underwent military medical examination.